Sedentary Behavior in Childhood, Lower Arterial Compliance and Decreased Endothelial Function-Cross Sectional Data From a German School Cohort - Böhm, Birgit; Kirchhuebel, Hannah; Elmenhorst, Julia; Müller, Jan; Oberhoffer-Fritz, Renate (Frontiers in Pediatrics, 2022)
Background Endothelial function by flow-mediated dilatation assesses early markers of atherosclerotic progression. Greater amounts of physical activity and physical fitness in children are associated with cardiovascular health benefits. We aimed to explore factors, influencing endothelial function and arterial compliance in a cohort of healthy school children. Methods The 94 participants (41 girls, 53 boys) in the study were young, healthy children from a German school cohort. Anthropometric data, body composition and blood pressure were assessed. Blood was drawn (8h overnight fast), assessing total cholesterol, high density lipoprotein and low density lipoprotein and triglycerides. Endothelial function was diagnosed by flow-mediated dilatation with ultrasonography (ALOKA/Hitachi, Prosound alpha 6). Tracking gates were set on the intima in B-mode. The waveform of diameter changes over the cardiac cycle was displayed in real time using the FMD-mode of the eTRACKING system. Changes in arterial diameter at baseline, ischaemia and vasodilatation were measured. A symptom limited pulmonary exercise test on a bicycle ergometer was performed to test cardiorespiratory fitness. Physical activity was assessed using GT3x accelerometers (Actigraph, USA), over 4 days (including 1 week-end day), with a minimum wear-time duration of 10 hours. Results The median age was 12.2 years (11.8 – 12.8). Children were normal weight, blood lipid profiles (cholesterol, high-density lipoprotein, low-density lipoprotein, triglyceride) were in normal range. Baseline measurements during the diagnostics of endothelial function revealed higher arterial compliance of the brachial artery in boys. Boys’ cardiorespiratory fitness was higher than compared to girls. Boys met the recommendations of 60 minutes moderate to vigorous activity, whereas girls were significantly less active and did not meet current recommendations. More time spent in sedentary activity was the main predictor for lower arterial compliance (adjusted for age and sex), accounting for 14% of the variance. No significant model revealed, analyzing the influencing factors such as anthropometric data, blood lipids, physical activity and fitness on endothelial function. Conclusion This is the first study on endothelial function in association to objectively measured physical activity and cardiorespiratory fitness in healthy school children in Germany. The study highlights the importance of reducing time spent being sedentary to maintain endothelial health.